PENGARUH FORMULASI SUKROSA DAN SIRUP GLUKOSA TERHADAP SIFAT KIMIA DAN SENSORI PERMEN SUSU KEDELAI [The Effect of Sucrose and Glucose Syrup Proportion on Chemical and Sensory Properties of Soymik Candy] - Sussi Astuti; zulferiyenni zulferiyenni; Ni Nyoman Yuningsih (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2015)
The objective of this research was to study the effect formulation between sucrose and glucose syrup on chemical and sensory properties of soymilk candy. The research was a single factor, arranged in a Complete Randomized Design with six replications. The factor was the formulation of sucrose and glucose syrup consisted of six levels, i.e. 100:0 (F1); 90:10 (F2); 80:20 (F3); 70:30 (F4); 60:40 (F5) and 50 : 50 (F6). The data were analyzed by using ANOVA and were tested with LSD test at 5% level of significant. The results showed that the ratio of sucrose and glucose syrup significantly affected the chemical properties (moisture content, ash content and reducing sugar content) and sensory (color, odor, taste, texture, and overall acceptance) of soymilk candy. The best formulation was found on soymilk candy produced from 60% sucrose and 40% glucose syrup (F5) with the color score of 2,49 (yellow-brown), odor score of 2,34 (rather specific soymilk), taste score of 3,12 (rather sweet), texture score of 3,24 (rather soft), and the overall acceptance score at 3,05 (like). The best soymilk candy has moisture content of 8,21%, ash content of 1,38% and reducing sugar content of 8,18%.Keywords : sucrose, glucose syrup, soymilk candy.